The Knowledge Practice Gap in Scabies Prevention among Female Students at Nurul Huda Islamic Boarding School, Mempawah - Selviana, Selviana; Karisma, Alvin Niami; Suwarni, Linda (Lembaga Penelitian dan Pemberdayaan Masyarakat, 2025)
Scabies remains a relevant public health problem in communal settings such as Islamic boarding schools, where crowding and shared daily facilities facilitate transmission. Although various health education activities have been implemented, field observations often show that increased knowledge does not automatically lead to sustained preventive practices. This study aimed to describe levels of knowledge and preventive behaviour related to scabies among female students and to highlight the gap between the two in the context of Nurul Huda Islamic Boarding School, Mempawah District. A descriptive cross-sectional design was applied with total sampling of 69 female students. Data were collected using a structured questionnaire covering knowledge about the cause, transmission, symptoms, and prevention of scabies, as well as preventive behaviours related to personal hygiene, clothing, towels, bedding, and the dormitory environment. Data were analysed descriptively and presented as frequencies and percentages. The findings show that most respondents had good knowledge of scabies, yet only about half demonstrated preventive behaviour in the good category. Risky practices, such as sharing beds and clothing and inconsistent management of clothes and bedding, remained relatively common. These results support the view that knowledge alone is insufficient to ensure consistent preventive behaviour, particularly in crowded environments with limited facilities and strong peer norms. The cross-sectional design, reliance on self-reported data, and absence of formal psychometric testing of the instrument limit the strength of inferences and point to the need for further, more analytical research on determinants of scabies-preventive behaviour in boarding school settings.